Students’ Achievement on Institutional TOEFL an Evaluation at FBS Universitas Wijaya Putra - Arjunani Arjunani; Yeni Probowati; Yulis Setyowati; Deni Kuswahono (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2021)
This study tries to describe students’ achievement on institutional TOEFL in Universitas Wijaya Putra. The test is meant as a means of evaluation upon the launching of a mandatory subject as a prerequisite towards final paper writing. The program begins with ten weeks of test preparation completed with a try-out test and the final test. This is a descriptive study since it tries to depict the result of their achievement and the most difficult section of the test. The data analysis uses the computation upon the results mostly applied for Excel Program, particularly in finding the Mean (X) and the Standard Deviation (S). The findings derived from the data analysis tell that  62.85% of the class belong to Grade D which means it is far below expectation. The finding also identified that Listening Section is to be the most difficult part of the test. Still, the findings say none of the students included into the level of either extremely excellent or failed. It is a big task to fulfill a better target for the coming classes by undergoing revision and development in many aspects, especially in time allocation and the module.